Recruitment of beneficial cucumber rhizosphere microbes mediated by amino acid secretion induced by biocontrol Bacillus subtilis isolate 1JN2 - Yang, Wei; Li, Xiao; Yan, Haixia; Sun, Yiwen; Wu, Diwen; Du, Ying; Luo, Yuming (Frontiers in Microbiology, 2024)
At present, the use of beneficial microorganisms to control cucumber Fusarium wilt is a widely used method, and the rhizosphere microecological reset is one of the mechanisms involved. However, how biocontrol strains reshape cucumber rhizosphere microecology remains to be further studied. In this study, cucumber plants were treated with biocontrol Bacillus subtilis 1JN2, which reduced the disease severity of Fusarium wilt by 60%. Significant changes in cucumber root exudates were found after treatment and the contents of four amino acids including glutamine, tryptophan, glycine and glutamic acid were significantly increased. Cucumber plants were treated with the above four amino acid mixture and biocontrol strain 1JN2 under greenhouse conditions, and the changes of bacterial population structure in cucumber rhizosphere were analyzed by high-throughput sequencing technology. It was found that the bacterial diversity in the rhizosphere of cucumber was significantly increased in both the strain treatment group and the amino acid mixture treatment group, The number of Bacillus was the largest in all dominant populations, exceeded 20% in all treatment groups. The bacteria of Hydrogenispora and Vicinamibacteria genus were significantly increased after treatment. Overall, the results demonstrated that amino acid substances in cucumber root exudates induced by biocontrol strain 1JN2 can reassembleshift the cucumber root microenvironment and prevent the occurrence of Fusarium wilt disease.